Novel Coronavirus: An Overview of the History, Pathophysiology, Diagnosis, and Management of the Pandemic COVID-19 Catastrophe, with Special Emphasis on Herbal Treatment Alternatives - Srivastava, Shikha; Parihar, Arun KS; Singh, Manju Rawat; Singh, Deependra; Chauhan, Nagendra Singh; Garabadu, Debapriya; Yadav, Krishna (Coronaviruses, 2025)
The crisis of COVID-19 pandemic, has shaken up the whole world with its power of transmission and unknown treatment strategy. A disease that starts with fever, cold, and cough leads to extreme fatigue, loss in breathing capacity, alveolar damage, and eventual death. The disease forced human beings to stay at home to protect humankind. Due to the serious nature of this COVID-19 pandemic, humankind was forced to understand the plausible cause and methods to reduce the spread and find out the best possible therapeutic regimen. Thus, the present review provided new insight into the history, symptoms, pathogenesis, diagnosis, clinical research, and follow-up treatment strategies of COVID-19. Further, In order to deal with such a pandemic situation, we have even introduced a novel concept of natural therapy based on medicinal plants for repurposing it as potential as a therapeutic warrior against COVID-19.
Keywords: pneumonia